Missouri River planning : recognizing and incorporating sediment management - National Research Council (U.S.). Committee on Missouri River Recovery and Associated Sediment Management Issues; National Research Council (U.S.). Water Science and Technology Board (Washington, D.C. : National Academies Press, 2011)
"Historically, the flow of sediment in the Missouri River has been as important as the flow of water for a variety of river functions. The sediment has helped form a dynamic network of islands, sandbars, and floodplains, and provided habitats for native species. Further downstream, sediment transported by the Missouri and Mississippi Rivers has helped build and sustain the coastal wetlands of the Mississippi River delta. The construction of dams and river bank control structures on the Missouri River and its tributaries, however, has markedly reduced the volume of sediment transported by the river. These projects have had several ecological impacts, most notably on some native fish and bird species that depended on habitats and landforms created by sediment flow. Missouri River Planning describes the historic role of sediment in the Missouri River, evaluates current habitat restoration strategies, and discusses possible sediment management alternatives. The book finds that a better understanding of the processes of sediment transport, erosion, and deposition in the Missouri River will be useful in furthering river management objectives, such as protection of endangered species and development of water quality standards"--Publisher's description
Changes in Missouri River sediment and related processes -- Missouri River governance : institutions, laws, and policies for managing sediment and related resources -- Sediment and current ecological restoration activities -- Sediment management alternatives and opportunities -- Water quality and Missouri River sediment management -- Science, policy, and future decision making along the Missouri River.
Includes bibliographical references (pages 129-141).
Print version record.
eBooks on EBSCOhost
Keywords: River sediments -- Missouri River Watershed; Sediment transport -- Missouri River Watershed; River engineering -- Environmental aspects -- Missouri River Watershed; Stream ecology -- Missouri River Watershed; Restoration ecology -- Missouri River Watershed; Missouri River; Sédiments fluviaux -- Missouri, Bassin du; Sédiments (Géologie) -- Transport -- Missouri, Bassin du; Technologie fluviale -- Aspect de l'environnement -- Missouri, Bassin du; Réhabilitation (Écologie) -- Missouri, Bassin du; Missouri (Rivière); SCIENCE -- Life Sciences -- Biological Diversity; NATURE -- Animals -- Wildlife; Restoration ecology; River engineering -- Environmental aspects; River sediments; Sediment transport; Stream ecology; Missouri River; Missouri River Watershed